UJI BAKTERIOLOGIS AIR MINUM PADA MATA AIR BUKIT SIKUMBANG DESA PULAU SARAK KECAMATAN KAMPAR - Kartini Winasari; Rita Endriani; Fifia Chandra (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTWater spring in Bukit Sikumbang Desa Pulau Sarak Kecamatan Kampar are used by people in the village to be sourced of drinking water. The water springs are appear from the land naturraly. The study aims to knowed bacteriological's quality of the drinking water from Bukit Sikumbang Desa Pulau Sarak Kecamatan Kampar's Water Springs. The method of this study was laboratoric description, the bacterological test had been collecting from 10 drinking water managing that sourced from Bukit Sikumbang's water springs by tap water that patch in distribution tub. The result showed that 100% sample contaminated by Coliform and 50% sample had positif result for containing Escherichia coli, so it did not fulfill the standart for health that had been established by Department of Health of Republic of Indonesia in